2021
DOI: 10.3390/ijerph18020401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strength vs. Plyometric Training Programs on Vertical Jumping, Linear Sprint and Change of Direction Speed Performance in Female Soccer Players: A Systematic Review and Meta-Analysis

Abstract: The main purpose of this systematic review and meta-analysis was to compare the effects of strength training (ST) and plyometric training (PT) on vertical jump, linear sprint and change of direction (COD) performance in female soccer players. A systematic search of the PubMed, Web of Science, Google Scholar and SportDiscus databases revealed 12 studies satisfying the inclusion criteria. The inverse-variance random-effects model for meta-analyses was used. Effect sizes (ES) were represented by the standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 58 publications
4
23
2
4
Order By: Relevance
“…To the best of our knowledge, the present investigation is the first to have studied the effects of a combined plyometric and short sprint training programs on start speed, in youth soccer players (U19). Our data are following the existing literature which has reported improved sprint performance after several programs, namely, combined plyometric and short sprints (Sáez de Villarreal et al, 2015 ; Almoslim, 2016 ; Hammami et al, 2019b ; Kargarfard et al, 2020 ), plyometric training (Hammami et al, 2019b ; Ramirez-Campillo and Sanchez-Sanchez, 2020 ; Pardos-Mainer and Lozano, 2021 ), and sprint training (Venturelli et al, 2008 ; Mujika et al, 2009 ; Rumpf et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…To the best of our knowledge, the present investigation is the first to have studied the effects of a combined plyometric and short sprint training programs on start speed, in youth soccer players (U19). Our data are following the existing literature which has reported improved sprint performance after several programs, namely, combined plyometric and short sprints (Sáez de Villarreal et al, 2015 ; Almoslim, 2016 ; Hammami et al, 2019b ; Kargarfard et al, 2020 ), plyometric training (Hammami et al, 2019b ; Ramirez-Campillo and Sanchez-Sanchez, 2020 ; Pardos-Mainer and Lozano, 2021 ), and sprint training (Venturelli et al, 2008 ; Mujika et al, 2009 ; Rumpf et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…The specialized literature highlights very few studies on football-tennis, and the many identified studies focus mainly on the management of the game and the technical training of football-tennis players [53,54]. We consider the results of our study to complete the conclusions of recent studies conducted on 12 football players [55], respectively, and on 40 football players [56], over a period of 8 months of endurance training combined with plyometric exercises/strength training program, which showed significant improvements in muscle strength and jump ability [57,58]. The level of explosive force can contribute to improving performance and sporting success.…”
Section: Discussionmentioning
confidence: 70%
“…Although intervention programs have been developed based on neuromuscular, plyometric, strength or power improvement training [31][32][33], there are discrepancies as to which exercises are the most effective in improving the performance of female soccer players. A recent review [34] has reported that plyometric training is more effective for improving vertical jump performance, linear sprint, and change of direction as compared to strength training in soccer players.…”
Section: Discussionmentioning
confidence: 99%